Dasar Pertimbangan Hukum Hakim Terhadap Putusan Perceraian Dengan Pemberian Hak Asuh Anak Kepada Ayahnya Menurut Hukum Positif Indonesia Dalam Perkara Nomor 4074/Pdt.G/2023/Pa.bdg Usulan Penelitian Hukum - Mulyadi Rusmana, Akbar; Saleh Indrapradja, Irwan (LPPM Universitas Ekasakti Padang, 2024)
This research is motivated by the fact that a husband cannot force a divorce. Instead, he must present his case to the court and the reasons why he wants to divorce his wife. The purpose of this research is to determine the basis of the judge's legal considerations regarding the divorce decision by granting custody of the child to the father according to Indonesian positive law in case number 4074/Pdt.G/2023/Pa.bdg Proposed Legal Research. This research uses descriptive analytical methods with a normative juridical approach. The results of the research show that a positive legal view regarding post-divorce child custody being given to the father is something that could happen if the father had more ability to care for and educate their child, but communication and agreement between parents is more important for their child's future. There are many other supporting factors for the judge to give custody of the child to the father after the divorce, such as the ability to look after him, educate him, provide a good and comfortable environment, and provide facilities to meet his biological mother. However, the facts that occurred during the trial are also the basis for the judge in deciding the case.